2021
DOI: 10.1371/journal.pone.0245010
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab versus intravitreal triamcinolone for diabetic macular edema–Systematic review, meta-analysis and meta-regression

Abstract: Background The most frequent cause of vision loss from diabetic retinopathy is diabetic macular edema (DME). Earlier clinical trials tried to examine the role of intravitreal triamcinolone (IVT) and intravitreal bevacizumab (IVB) in DME; they either qualified IVT over IVB or IVB over IVT or did not exhibit a significant difference. Objective This paper aims to compare the efficacy and safety of IVB versus IVT alone or combined IVB+IVT in the treatment of DME. Methods We systematically searched PubMed, CENT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Hunt et al demonstrated a fixed protocol of 12-month intravitreal bevacizumab injections consisting of five consequent injections of 1.25 mg/0.05 mL followed by four injections every other month and showed a significant improvement in BCVA and reduction in central macular thickness 34 . Multiple injections of bevacizumab also had a (statistically significant) greater improvement in BCVA compared to intravitreal triamcinolone and a combination of intravitreal triamcinolone with bevacizumab 5 . Bevacizumab is more expensive than ranibizumab or aflibercept.…”
Section: Anti-vegf Drugs Mechanism and Efficacymentioning
confidence: 84%
See 2 more Smart Citations
“…Hunt et al demonstrated a fixed protocol of 12-month intravitreal bevacizumab injections consisting of five consequent injections of 1.25 mg/0.05 mL followed by four injections every other month and showed a significant improvement in BCVA and reduction in central macular thickness 34 . Multiple injections of bevacizumab also had a (statistically significant) greater improvement in BCVA compared to intravitreal triamcinolone and a combination of intravitreal triamcinolone with bevacizumab 5 . Bevacizumab is more expensive than ranibizumab or aflibercept.…”
Section: Anti-vegf Drugs Mechanism and Efficacymentioning
confidence: 84%
“…Analysis done by Bhandari et al presented that patients, on average, received four to nine injections over the year, which resulted in patients gaining better VA (7-9 letters) 33 . Multiple injections were given, with a 4-6-week interval 5 . Hunt et al demonstrated a fixed protocol of 12-month intravitreal bevacizumab injections consisting of five consequent injections of 1.25 mg/0.05 mL followed by four injections every other month and showed a significant improvement in BCVA and reduction in central macular thickness 34 .…”
Section: Anti-vegf Drugs Mechanism and Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported in a fiveyear extension of the same study that the increasement of IOP incidence was 79%, the initiation of IOP-lowering medication was 56%, 3% of cases called for glaucoma surgery, and the occurrence of cata racts was 71% [26] . In Abdel-Maboud et al's [27] Meta-analysis, at 36 and 48wk follow-up, the intravitreal bevacizumab (IVB) group was lower IOP than the IVTA group with a statistically significance. In addition, when compared with IVTA or IVB+IVTA, the group who received IVB showed a significant lower intraocular hypertension (IOH) incidence.…”
Section: Discussionmentioning
confidence: 97%
“…57 Being the first suggested anti-VEGF for ROP, Bevacizumab is a recombinant monoclonal antibody used to treat several cancers such as glioblastoma, renal, colon, and lung carcinomas when given systematically; and macular degeneration or retinopathy, when given intravitreally. 58,59 Other Anti-VEGF agents include intravitreal ranibizumab (IVR) and intravitreal aflibercept (IVA). 60 After the findings of the Bevacizumab Eliminates the Angiogenic Threat of Retinopathy of Prematurity (BEAT-ROP) study, anti-VEGF agents gained more credentials in treating ROP.…”
Section: Vegf Inhibitorsmentioning
confidence: 99%